IMPLEMENTATION OF THE SISKEUDES APPLICATION IN VILLAGE FINANCIAL MANAGEMENT IN KAJEKSAN VILLAGE - Syavitri, Nadiya Ami; Agustina, Isna Fitria (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the implementation of the Village Financial System (Siskeudes) application in Kajeksan Village, Tulangan District, Sidoarjo Regency, using George C. Edward III’s public policy implementation theory, which includes the indicators of communication, resources, disposition, and bureaucratic structure. Method: This research employed a descriptive qualitative approach, with data collection techniques consisting of interviews, observations, and documentation. Informants were selected using purposive sampling, focusing on the Siskeudes operator in Kajeksan Village as the main source of information. Results: The findings indicate that communication between the local government and the village is conducted through training and socialization sessions whenever system updates occur. In terms of resources, village officials have received technical training, enabling knowledge transfer, and financial management is handled by more than one person. Budget allocations cover device maintenance and the procurement of digital administrative needs, although challenges remain with the stability of the internet connection. Regarding disposition, the operator records each financial activity, addresses technical issues, and verifies data before submitting reports. The bureaucratic structure supports implementation through a clear division of tasks and the availability of SOPs, although internal evaluations have not yet been conducted regularly. Novelty: The novelty of this study lies in its specific focus on the implementation of Siskeudes in Kajeksan Village, which has not been previously examined.